Effects, equity, and cost of school-based and community-wide treatment strategies for soil-transmitted helminths in Kenya: a cluster-randomised controlled trial. Issue 10185 (18th May 2019) - Pullan, Rachel L; Halliday, Katherine E; Oswald, William E; Mcharo, Carlos; Beaumont, Emma; Kepha, Stella; Witek-McManus, Stefan; Gichuki, Paul M; Allen, Elizabeth; Drake, Tom; Pitt, Catherine; Matendechero, Sultani H; et al.
Summary: Background: School-based deworming programmes can reduce morbidity attributable to soil-transmitted helminths in children but do not interrupt transmission in the wider community. We assessed the effects of alternative mass treatment strategies on community soil-transmitted helminth infection. Methods: In this cluster-randomised controlled trial, 120 community units (clusters) serving 150 000 households in Kenya were randomly assigned (1:1:1) to receive albendazole through annual school-based treatment targeting 2–14 year olds or annual or biannual community-wide treatment targeting all ages. The primary outcome was community hookworm prevalence, assessed at 12 and 24 months through repeat cross-sectional surveys. Secondary outcomes were Ascaris lumbricoides and Trichuris trichiura prevalence, infection intensity of each soil-transmitted helminth species, and treatment coverage and costs. Analysis was by intention to treat. This trial is registered with ClinicalTrials.gov, number NCT02397772 . Findings: After 24 months, prevalence of hookworm changed from 18·6% (95% CI 13·9–23·2) to 13·8% (10·5–17·0) in the annual school-based treatment group, 17·9% (13·7–22·1) to 8·0% (6·0–10·1) in the annual community-wide treatment group, and 20·6% (15·8–25·5) to 6·2% (4·9–7·5) in the biannual community-wide treatment group. Relative to annual school-based treatment, the risk ratio for annual community-wide treatment was 0·59 (95% CI 0·42–0·83; p<0·001) and for biannual community-wide treatment was 0·46 (0·33–0·63; p<0·001). More modest reductions in risk were observed after 12 months. Risk ratios were similar across demographic and socioeconomic subgroups after 24 months. No adverse events related to albendazole were reported. Interpretation: Community-wide treatment was more effective in reducing hookworm prevalence and intensity than school-based treatment, with little additional benefit of treating every 6 months, and was shown to be remarkably equitable in coverage and effects. Funding: Bill & Melinda Gates Foundation, the Joint Global Health Trials Scheme of the Medical Research Council, the UK Department for International Development, the Wellcome Trust, and the Children's Investment Fund Foundation.